Using parametric and non-parametric tests to identify the development of the scientific level for the academic years 2012-2016 - Fayyad Abdullah Ali; Ala Hadi Sadiq (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Under hard conditions that prevailed in Iraq in recent years, we note changes in various aspects of social, economic, and security of life and the changes to these aspects did not stop, but went on to include the scientific aspect and try to catch a scientific look at the university actually been preparing this research to study the evolution of the scientific level of students in Wasit University last five years 2012-2016 to achieve this goal took a sample of students from the Department of Statistics (phase IV) and chosen statistical inference (as to measure individual differences) using a number of parametric tests and tests Nonparametric tests which showed that there are low at the scientific level necessary to stop him, and the study of causes for the purpose of handling.